PENGARUH BUDAYA KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA ASN PADA KANTOR SEKRETARIAT DAERAH KABUPATEN POLEWALI MANDAR - Kaharullah - Ismail; Maryadi Maryadi; Asri Asri (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2022)
This study aims to analyze the effect of motivation, commitment and leadership style partially and simultaneously on employee work discipline and to analyze the variables that have the most dominant influence on the Department of Agriculture and Food, Polewali Mandar Regency. The research used in this study is a quantitative research method. The population in this study were employees of Agriculture and Food Office of Polewali Mandar Regency, totaling 114 civil servants. Sampling of this study was carried out using the slovin technique with a significant standard of 5%. Thus, it can be seen that the sample used in this study were employees of Agriculture and Food Office of Polewali Mandar Regency totaling 89 respondents. The data collection technique was carried out through a questionnaire/questionnaire where each respondent's answer was assessed using a score according to the Likert scale. The results of this study indicate that the results of the F test or simultaneous testing indicate that the Fcount value is 36.711 and Ftable is 2.71. So it shows that Fcount > Ftable with a significance of 0.000 < 0.05. These results indicate that motivation, commitment and leadership style simultaneously have a significant effect on the work discipline of the employees of the Department of Agriculture and Food, Polewali Mandar Regency. From the description of the t test, it is known that motivation, commitment and leadership style partially each have a positive and significant effect on the work discipline of the employees of the Department of Agriculture and Food, Polewali Mandar Regency. Furthermore, the motivation variable is the most dominant influencing variable with a beta value of 0.512.